Det næstekærlige fællesskab: Bemærkninger til kristendommens selv-dekonstruktion - Kasper Lysemose (Religionsvidenskabeligt Tidsskrift, 2017)
The paper presents the self-deconstruction of Christianity in the guise of two claims: i. The God withdrawn is part in a community of those who are abandoned by God – namely as the ‘with’ of their being-with. ii. Christian love is the reserve in Christianity that exposes us to this very being-with – i.e. to something in Christianity “older” than Christianity itself. Jean-Luc Nancy’s general ontology of being-with and its specific configuration as a ‘deconstruction of Christianity’ is introduced. Subsequently this deconstruction is traced in The Works of Love by Søren Kierke-gaard.